2020
DOI: 10.1002/erv.2719
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characterisation of pregnant women with eating disorders

Abstract: Objective: To estimate prevalence of lifetime and current eating disorders (ED) in a sample of pregnant women in South-East London and to describe their sociodemographic and clinical characteristics.Method: Secondary analysis of data from a cross-sectional survey. Using a stratified sampling design, 545 pregnant women were recruited. Diagnostic interviews were administered to assess lifetime and current ED, depression, anxiety, and borderline personality disorder. Data were extracted from maternity records to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
0
25
0
2
Order By: Relevance
“…Remarkably, the occurrence of eating disorders (anorexia nervosa, bulimia nervosa, binge eating disorders, eating disorders not otherwise speci ed…) during pregnancy was of a wide divergence between studies, ranging from 0.6% to not lesser than 27.8% [8][9][10][11][12][13][14][15][16][17][18] . These disparities could be explained by the diversity of assessment tools, varying from self-reported questionnaires (based on adapted versions of pre-existing scales for eating disorders, or designed on items derived from the DSM-4 or DSM-5 criteria) to structured interviews 9 , hence emphasizing the need for an international consensual and accurate pregnancy-speci c screening tool, as previously suggested by a Delphi study 19 , to make comparisons easier in research, and to minimize the probability of false negative and false positive tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the occurrence of eating disorders (anorexia nervosa, bulimia nervosa, binge eating disorders, eating disorders not otherwise speci ed…) during pregnancy was of a wide divergence between studies, ranging from 0.6% to not lesser than 27.8% [8][9][10][11][12][13][14][15][16][17][18] . These disparities could be explained by the diversity of assessment tools, varying from self-reported questionnaires (based on adapted versions of pre-existing scales for eating disorders, or designed on items derived from the DSM-4 or DSM-5 criteria) to structured interviews 9 , hence emphasizing the need for an international consensual and accurate pregnancy-speci c screening tool, as previously suggested by a Delphi study 19 , to make comparisons easier in research, and to minimize the probability of false negative and false positive tests.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the occurrence of eating disorders (anorexia nervosa, bulimia nervosa, binge eating disorders, eating disorders not otherwise speci ed…) during pregnancy was of a wide divergence between studies, ranging from 0.6% to not lesser than 27.8% [8][9][10][11][12][13][14][15][16][17][18] . These disparities could be explained by the diversity of assessment tools, varying from self-reported questionnaires (based on adapted versions of pre-existing scales for eating disorders, or designed on items derived from the DSM-4 or DSM-5 criteria) to structured interviews 9 , hence emphasizing the need for an international consensual and accurate pregnancy-speci c screening tool, as previously suggested by a Delphi study 19 , to make comparisons easier in research, and to minimize the probability of false negative and false positive tests. On top of that, a recent systematic review refuted the suitability of the traditional existing measures for evaluating eating disorders in pregnancy, pointing out that among sixteen scales applied across countries, not more than four were presented along with documented psychometric characteristics, yet none was able to stand up for a meritorious level of clinical pertinence (in terms of psychometric performance as internal consistency, criterion-related validity, screening accuracy…) to the point of being set as a "gold standard" measure or substituting the need for a speci cally conceived instrument for identifying dysfunctional eating symptoms during pregnancy 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Eating disorders have the highest rate of mortality of any mental disorder. A recent study of UK inner city women found a prevalence rate of 1.47% in pregnancy but detection rates by maternity staff were low [21]. There is evidence that abnormal eating attitudes and behaviours may lessen during pregnancy but worsen again in the postnatal period.…”
Section: Other Mental Disordersmentioning
confidence: 99%
“…Essstörungen sind eine heterogene Gruppe schwerer psychischer Erkrankungen, darunter Anorexia nervosa, Bulimia nervosa und Binge-Eating-Störung, die durch gestörtes Ess-oder Gewichtskontrollverhalten gekennzeichnet sind, welche die körperliche Gesundheit und die psychosoziale Funktionsfähigkeit erheblich beeinträchtigen können [9]. Populationsbasierte Kohortenstudien zeigen Prävalenzen von Essstörungen bei 1,5-7,6 % der schwangeren Frauen [10]. Studien mit schwangeren Frauen identifizieren 4 wesentliche Aspekte, die in Zusammenhang mit einer Vorgeschichte von Essstörungen relevant sind: 1.…”
Section: Essstörungenunclassified